Proximal migration of Plastibell circumcision: two case reports and review of the literature - Ali M. Ahmad; Sara Elfadil Ahmed; Noha Ali Mostafa; Turki Ibrahim Nafisah (SpringerOpen, 2022)
Abstract Background Male circumcision is one of the oldest and most commonly performed surgical procedures in the world; in fact, one of every 3 males in the world is circumcised. Plastibell circumcision is the commonest procedure performed worldwide with higher rates of satisfaction and lower rates of complications. Case presentation We present two cases, 4 and 5 months old with proximal migration of Plastibell ring with penile incarcerations that were managed successfully. We aim to highlight the necessary precautions needed to avoid serious complications after a minor surgical procedure. Conclusions Plastibell circumcision is a minor surgical procedure that is underestimated with the potential for major and serious complications. The implementation of the law against the practice of non-professional individuals, standardization of the procedure, and improvement of communication are highly recommended to avoid unnecessary and serious complications. Plastibell ring circumcision still needs further studies to examine ring antimigration, re-designing, and the best types and sizes of threads used. Lastly, studies are also needed to determine a cost-effective routine follow-up visit post-Plastibell circumcision procedures.